Immune response in infants after universal hepatitis B vaccination: a community-based study in Malaysia - Lee, W.S.; Cheang, H.K.; Wong, H.T.; Ho, S.C.; Chew, K.S. (Stamford Publishing Pte Ltd, 2013)
This study aimed to assess the immune response in infants who received the three-shot hepatitis B vaccine in Malaysia. Consecutive infants born between March 2002 and April 2010 who received three doses of hepatitis B vaccine at a community clinic in Malaysia were enrolled in the study. Screening for hepatitis B surface antigen (HBsAg) and antibody against HBsAg (anti-HBs) was performed after the completion of primary immunisation, at approximately one year of age. A total of 572 infants (median age 9.3 ± 2.7 months; range 6.3–48 months) were screened for immune response to hepatitis B vaccination – 553 (96.7%) infants had adequate levels of anti-HBs (≥ 10 IU/L). Of the 440 mothers whose HBsAg status was known, 14 (3.2%) were positive for HBsAg. None of the 14 infants who were born to HBsAg-positive mothers were positive for HBsAg, and all but one infant had anti-HBs level ≥ 10 IU/L. Gender, gestational age and maternal HBsAg status were not found to significantly affect the subsequent immune response in infants following vaccination. The proportion of Malaysian mothers who are positive for HBsAg remains high. The three-shot hepatitis B vaccine, given as part of universal vaccination against hepatitis B, provides adequate anti-HBs in the vast majority of infants in a community setting in Malaysia.